Patogenia gastritei - O abordare completă a mecanismelor patologice, a modificărilor histologice, de la nivelul mucoasei gastrice și clasificarea leziunilor gastrice - Sergiu Aurel Alic Orasan; Răzvan F. Moruzi; Eugenia Dumitrescu; Florin Muselin; Alexandru O. Doma; Corina Vlad; Mihai Folescu; Romeo T. Cristina (Medicamentul Veterinar)
This manuscript details the pathological mechanisms of the establishment of gastric ulceration, and details its stages, both in terms of mechanisms of action and in terms of histological changes found in the gastric mucosa. Also, a synthesis is made of all types of gastritis classification, established diagnostic methods, and histological evaluation of gastric tissue by biopsy, developed in the last five decades globally in human use, which can also help to introduce them into veterinary medicine. The last part of the article is dedicated to established experimental models of gastric ulcer induction, in laboratory animals (mice/rats), supporting young researchers/veterinary or human doctors, for the development of new drug formulations with as few adverse effects as possible and low costs for both human and veterinary medicine.